Ambiguous Loss and Its Disenfranchisement: The Need for Social Work Intervention. Issue 2 (April 2019) - Knight, Carolyn; Gitterman, Alex
Ambiguous grief results from a nondeath loss and has received minimal attention in the social work literature. This type of loss occurs in situations like missing persons, incarceration, military deployment, adoption, and foster care and chronic conditions like dementia. The reactions of loved ones faced with these situations rarely have been understood as a form of grief. The lack of recognition of ambiguous loss means that it is more likely to be disenfranchised, which undermines bereaved individuals' resilience and ability to move on with their lives. The authors discuss the nature of ambiguous loss and its disenfranchisement. Based upon theory and research, implications for micro-, mezzo-, and macropractice are presented. Case examples illustrate key points and challenges.